Pengaruh Job Embeddedness dan Kepuasan Kerja Terhadap Turnover Intention - Garnita, Made Ayu; Suana, I Wayan (E-Jurnal Manajemen, 2014)
This purpose of this research is to determine the effect of job embeddedness and job satisfaction on turnover intention sales staff  at PT. Bali Petshop & Grooming. Turnover intention is influenced by several factor , such as job embeddedness and job satisfaction. Data from 34 respondents obtained by census method and analyzed using multiple linear regression. Data was collected by questionarre, observation and interview. The results of this research shows that job embeddedness and job satisfaction negatively and significantly simultaneously or partially effect on turnover intention.
Keywords: Job Embeddedness, Job Satisfaction, Turnover Intention